2017
DOI: 10.3892/ijmm.2017.3351
|View full text |Cite
|
Sign up to set email alerts
|

KDM3A inhibition attenuates high concentration insulin‑induced vascular smooth muscle cell injury by suppressing MAPK/NF‑κB pathways

Abstract: Previous studies have indicated that lysine (K)-specific demethylase 3A (KDM3A) is associated with diverse diabetes-associated cardiovascular complications in response to high glucose levels. However, the effects of KDM3A on the pathological progression of cardiovascular injuries in response to high insulin levels remain unknown. The present study aimed to explore whether KDM3A knockdown may attenuate high insulin-induced vascular smooth muscle cell (VSMC) dysfunction, and to further investigate the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Our initial studies showed that KDM3A could promote vascular neointimal hyperplasia in diabetic rats via the AGTR1 and ROCK2 signalling pathways . KDM3A inhibition could also attenuate high concentration insulin–induced vascular smooth muscle cell injury by suppressing MAPK/NF–κB pathways . In addition, our latest findings suggest that KDM3A is involved in diabetic cardiomyopathy and is a crucial factor in mediating myocardial ‘Metabolic Memory’ injury in diabetes by facilitating NF‐κB/p65 transcriptional activities.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Our initial studies showed that KDM3A could promote vascular neointimal hyperplasia in diabetic rats via the AGTR1 and ROCK2 signalling pathways . KDM3A inhibition could also attenuate high concentration insulin–induced vascular smooth muscle cell injury by suppressing MAPK/NF–κB pathways . In addition, our latest findings suggest that KDM3A is involved in diabetic cardiomyopathy and is a crucial factor in mediating myocardial ‘Metabolic Memory’ injury in diabetes by facilitating NF‐κB/p65 transcriptional activities.…”
Section: Discussionmentioning
confidence: 81%
“…15 KDM3A inhibition could also attenuate high concentration insulin-induced vascular smooth muscle cell injury by suppressing MAPK/NF-κB pathways. 17 In addition, our latest findings suggest that KDM3A is involved in diabetic cardiomyopathy and is a crucial factor in mediating myocardial 'Metabolic Memory' injury in diabetes by facilitating NF-κB/p65 transcriptional activities. Moreover, our unpublished research also indicated that KDM3A played an important role in myocardial ischaemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A prior study has yielded similar results demonstrating that miR-130b expression was elevated in GC tissues relative to matched normal tissues, and that the upregulated miR-130b promoted cell viability and reduced death of GC cells [ 30 ]. Another study likewise showed increased miR-130b-5p expression in GC cell lines, and that GC cells with overexpressed miR-130b-5p had potentiated cell proliferation, colony formation, as well as migratory and invasive capacities [ 31 ]. High expression of other miRNAs, such as miR-130, has been observed in advanced GC tissues, which was similarly associated with risk for distant metastasis, lymph node metastasis, and poor long-term survival [ 28 ].…”
Section: Discussionmentioning
confidence: 99%